2016
DOI: 10.1002/jqs.2871
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of hydrogen, oxygen and carbon isotope variability inSphagnummoss along a micro‐topographical gradient in a southern Patagonian peatland

Abstract: Peat archives offer a diverse range of physical and chemical proxies from which it is possible to study past environmental and ecological changes. Direct numerical calibration and verification is difficult so process-based and mechanistic studies are therefore required to establish and quantify links between environmental changes and their associated proxy-responses. Traditional 'space-for-time' calibrations provide a solution to this calibration problem, but are often unable to isolate a single environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 69 publications
(95 reference statements)
2
22
1
Order By: Relevance
“…Likewise, this negative correlation was also found from another similar study at a Sphagnum-dominated peatland site in southernmost Patagonia ( Fig. DR5; Loader et al, 2016). Many studies on carbon isotope composition of mosses concluded that moisture availability exerts a critical influence (Rice and Giles, 1996;Price et al, 1997;Ménot and Burns, 2001;Loisel et al, 2009), although other studies indicated potential influence of temperature, probably due to intrinsic relation between temperature and moisture-related environmental factors (e.g., Ménot and Burns, 2001;Moschen et al, 2011).…”
Section: Evaluation Of Evaporative Effect On Oxygen Isotopes Of Moss supporting
confidence: 76%
“…Likewise, this negative correlation was also found from another similar study at a Sphagnum-dominated peatland site in southernmost Patagonia ( Fig. DR5; Loader et al, 2016). Many studies on carbon isotope composition of mosses concluded that moisture availability exerts a critical influence (Rice and Giles, 1996;Price et al, 1997;Ménot and Burns, 2001;Loisel et al, 2009), although other studies indicated potential influence of temperature, probably due to intrinsic relation between temperature and moisture-related environmental factors (e.g., Ménot and Burns, 2001;Moschen et al, 2011).…”
Section: Evaluation Of Evaporative Effect On Oxygen Isotopes Of Moss supporting
confidence: 76%
“…Loader et al (2016) reported a similar slope estimate for S. magellanicum in a single peatland and several studies have confirmed effects of contrasting microtopography (i.e. hummock-hollow differences) using multi-species comparisons (Price et al 1997, Loisel et al 2009, Markel et al 2010).…”
Section: Stable Carbon Isotope Discrimination In Sphagnummentioning
confidence: 70%
“…Because peat decomposes slowly and gradually accumulates, it preserves information on past peatland ecosystem dynamics and responses to allogenic and autogenic forcing. Palaeoenvironmental studies of peat may, therefore, help anticipate future response of these globally important ecosystems to climate change (Loader et al 2016). Past climate and local hydrology can be estimated using a variety of biotic and biogeochemical proxies, including the δ Royles et al 2016, Lamentowicz et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations